PERENCANAAN PENANGKAL PETIR DI GEDUNG SEKOLAH TINGGI TEKNOLOGI PEKANBARU - Ermawati; Engla Harda Arya (Jurnal Surya Teknika, 2021)
The installation of lightning rods is very necessary for office buildings, buildings, towers so that humans and equipment inside the building are protected from the danger of lightning strikes. This study plans a good lightning rod to be installed in the Pekanbaru Technology High School building by knowing the values ​​of lightning strike density, lightning strike distance, the level of building hazard estimates, determining the area that attracts lightning strikes, determining the number of lightning strikes per year, and determining the radius. protection against lightning strikes. The results of the research that has been carried out, in the Pekanbaru Technological School (STTP) building with a building length of 32.50 m, a building width of 22.50 m, and a building height of 18.00 m. obtained the value of lightning density N_g=35,3602 km²/year, area of ​​attraction for lightning strikes A_e=15,827.49 m², the number of lightning strikes N_d=0,559/year, has level III protection with E=082, area of ​​radius A_x=174.885.44 m², So to be safer from lightning strikes, the STTP building using an electrostatic lightning rod is enough to use 1 finial with a length of 2 m.